Research of water extraction from xenoderm as an active pharmaceutical ingredient in drugs - B. V. Pavliuk; Yu. Ya. Melnyk; Т. А. Hroshovyi; М. B. Chubka; V. Y. Skorokhoda (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Today, burns are one of the most common types of injuries in the home and at work around the world. Therefore, the issue of treatment of burns remains relevant today for medicine and pharmacy in particular. In Ukraine, the method of treatment of burns using xenodermoimplants from porcine skin is used, and therefore the crushed substrate of cryolyophilized porcine skin (xenoderm) is a promising active ingredient in the technology of various drug forms. The aim of the work was to study the structural and mechanical properties of water extract from the crushed substrate of the xenoderm and to determine its amino acid composition by using physicochemical analysis, namely using high performance liquid chromatography (HPLC). A glass pycnometer and a Heppler BH 2 MLW drop ball viscometer were used to determine the density and viscosity of the water extract from the xenoderm. The density and viscosity of the water extract were studied at different temperatures. The dependence of the density and viscosity of the water extract from the xenoderm on temperature was studied and it was found that with increasing temperature the dynamic viscosity decreases and the density changes slightly. A glass pycnometer and a viscometer with falling ball were used to determine the density and viscosity of the xenoderm water extract. Chromatographic separation of amino acids was performed on a liquid chromatograph Agilent 1200 with a fluorescent detector. Chromatographic determination of amino acids was performed on a liquid chromatograph Agilent 1200 (USA) with a fluorescent detector G1315A (USA) and an autosampler 1313A. Using the HPLC method, 16 amino acids were identified (essential - 6; conditionally - 2; nonessential - 8). Identified amino acids are almost in a bound state (1.5%), the largest amount is glutamic acid (0.23%), glycine (0.19%), aspartic acid (0.18%), proline (0.17%) and arginine (0.17%). In unbound form, the content of glutamic acid (0.09%) and glycine (0.06%) is the highest. Based on the results of research, you can choose quality indicators, to determine the appropriate criteria that can be proposed for the standardization of water extract from the crushed substrate of the xenoderm.